The Economic Achievements of Polish Diaspora in Manchuria an Inner Mongolia, 1898-1936 - Borysiewicz, Mariusz (Res Historica, 2019)
For a century and a half the Far East, including Inner Mongolia and Manchuria was the scene of endless wanderings and long sojourns of political exiles from Poland, whom Russian tyranny drove into that wilderness, and many of whom made significant contributions to the economic development of that part of Asia. In the course of time numerous Poles – partly political exiles and partly voluntary emigrants, being gifted with a spirit of enterprise – built up large industrial undertakings and made great fortunes, both in sparsely populated steppes of Inner Mongolia and vast forests of Northeastern China. Such were, for instance, the industrialist Władysław Kowalski (1870–1940) and the mining engineer Kazimierz Grochowski (1873–1937). Both of them were prominent representatives of the Polish diaspora in Manchuria and Inner Mongolia. Kowalski, widely respected by other diasporas in the area, made millions in business and became one of the most influential manufacturers as well as philanthropists across Manchuria. Grochowski, on the other hand, supervised the geological survey on the Amur, on Sakhalin and in Inner Mongolia, and found petroleum in Manchuria. The presence of Polish community in Manchuria and Inner Mongolia cannot be separated from the Russian-built Chinese Eastern Railway that linked Siberia with North China and drew people from the far reaches of the Tsarist Russia in their tens of thousands to the largely wild and uncharted region in the borderland between Russia, Inner Mongolia and Manchuria. Daleki Wschód, w tym Mongolia Wewnętrzna i Mandżuria, przez ponad półtora wieku był miejscem niekończącej się tułaczki i długoletniej zsyłki Polaków, których rosyjska tyrania wygnała na nieznane odludzia. Jednocześnie wielu z nich przyczyniło się do rozwoju gospodarczego tej części Azji. W miarę upływu czasu znacząca ilość Polaków – częściowo zesłańców politycznych, a częściowo dobrowolnych emigrantów obdarzonych duchem przedsiębiorczości – dorobiła się fortuny i zarazem przyczyniła się do budowy dużych manufaktur, zarówno na terenie słabo zaludnionych stepów Mongolii Wewnętrznej, jak i rozległych lasów północno-wschodnich Chin. Przykładem tego mogą być losy przedsiębiorcy Władysława Kowalskiego (1870-1940) i inżyniera Kazimierza Grochowskiego (1873-1937), którzy byli wybitnymi przedstawicielami polskiej diaspory w Mandżurii i Mongolii Wewnętrznej.